PENGARUH PEMBENTUKAN TEGANGAN SISA PADA HASIL PENGELASAN - Mamang Magga (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2009)
There are three methods that are usually done to measure residual stress, namely sectioning, hole drilling, X-tray methods. By using one of the methods, characteristic and effect of welding residual stress can be done. Formation of residual stress is affected by constrain of transformation and melting material, high temperature of heat, cooling rate, and external stress. In addition, the highest residual stress can be found at welding and Heat Affected Area (HAZ).